2020
DOI: 10.1002/ecj.12277
|View full text |Cite
|
Sign up to set email alerts
|

Estimation model of muscle fatigue based on muscle fiber type using electromyography

Abstract: In muscle rehabilitation and training, it is important to evaluate a patient's muscle state. In general, training is based on physical therapy, but there has not been quantitative assessment of the actual effects on muscles. The authors previously tried to quantify muscle fatigue and defined “Muscle‐fatigue time (MFT)” as the quantitative evaluation index of muscle fatigue based on electromyography and the use ratio of the muscle fiber type. MFT is the time when the use ratio of the slow muscle fiber (Type I) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that grip force can be employed as a reliable indicator of muscle weakness in the upper limbs during the chronic post-stroke period [ 23 ]. Additionally, sEMG can accurately reflect local muscle fatigue in the human body [ 24 ] and is an effective way of tracking and evaluating muscle coordination [ 25 ], predicting forearm movements [ 26 ] and joint angle [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that grip force can be employed as a reliable indicator of muscle weakness in the upper limbs during the chronic post-stroke period [ 23 ]. Additionally, sEMG can accurately reflect local muscle fatigue in the human body [ 24 ] and is an effective way of tracking and evaluating muscle coordination [ 25 ], predicting forearm movements [ 26 ] and joint angle [ 27 ].…”
Section: Introductionmentioning
confidence: 99%